Urban Water Cycle Modelling and Management - Meenakshi Arora (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Many major cities of the world face challenges arising from growing and urbanizing populations, a changing climate, and an increase in the frequency of extreme weather events. Existing centralized water services, operating at, or close to, full capacity, are not sufficient to cope with the associated increase in water demand. Replacing the entire centralized infrastructure is very difficult within the existing environmental and economic constraints. Water services can be provided through the integration of decentralized and centralized systems, which are referred to herein as hybrid water supply systems. This Special Issue presents 12 papers encompassing various aspects including challenges and experiences associated with innovations in urban water cycle management. These papers straddle physical and policy research on implementation topics. Five papers fall in the area of systems modelling, two papers deal with design criteria issues of new and modified systems, one paper is of an experimental nature and another focuses on the impact of urban systems on the estuarine environment, while two papers deal with policy and risks. The papers included in this Special Issue emanated from a large number of submissions that were subjected to a thorough peer-review process. For this effort, we thank all the authors and reviewers that have contributed to this endeavour.